The role of relationships versus reputation in determining perceptions of employer attractiveness : a case-based study into how employer brand perception is formed in the health industry - Archer, Catherine Jane (Curtin University, 2008)
In Australia and many other developed countries, there have been acute skills shortages in a number of different industries. Even with the current economic downturn, healthcare continues to have a shortfall in staffing. Building a strong employer brand offers a promising approach to this problem. Employer branding is the “package of functional, economic and psychological benefits provided by employment and identified with the employing company” (Ambler & Barrow 1996, p. 187). Using a qualitative approach, this case study of a private hospital in Australia explores the role of these concepts in building a strong employer brand. The purpose of this study is threefold: first, to identify which is more important in influencing a company’s employer brand – its reputation or relationships; second, to analyse perceptions of employer branding for nurses at different levels of their career; and third, to identify the barriers to implementing the employer branding/attractiveness concept in the health industry. A large, for-profit private hospital within Western Australia was investigated, focusing on the nursing profession. It was found that a company’s relationships with its stakeholders will have a direct influence on a company’s reputation.Therefore, the two concepts are more closely related than the existing literature (e.g. Hutton 1999) would suggest. Relationships prior to (and during) employment were seen as an important factor in projecting an attractive employer brand, a factor not previously emphasised in the employer branding literature. It was found that perceptions of factors related to employer attractiveness did differ depending on experience and life stage. However, over-promising in recruitment was identified by all employees interviewed as a major source of disenchantment. The concept of “reputation” was reviewed and it was found that negative visibility appeared to have a stronger impact than a positive reputation. Reputation was often formed via word-of-mouth from industry colleagues, hence the importance of developing strong relationships as a major step to ensuring a quality reputation. Within management there were several barriers to an effective employer branding process identified. The thesis concludes with a discussion of the implications and limitations of this study, together with recommendations for future research.